2017
DOI: 10.1124/jpet.117.241125
|View full text |Cite
|
Sign up to set email alerts
|

Jadomycins Inhibit Type II Topoisomerases and Promote DNA Damage and Apoptosis in Multidrug-Resistant Triple-Negative Breast Cancer Cells

Abstract: Jadomycins are natural products that kill drug-sensitive and multidrug-resistant (MDR) breast cancer cells. To date, the cytotoxic activity of jadomycins has never been tested in MDR breast cancer cells that are also triple negative. Additionally, there is only a rudimentary understanding of how jadomycins cause cancer cell death, which includes the induction of intracellular reactive oxygen species (ROS). We first created a paclitaxel-resistant, triple-negative breast cancer cell line [paclitaxel-resistant MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(75 citation statements)
references
References 46 publications
0
75
0
Order By: Relevance
“…These attributes include its capacity to act as a nucleophile (and therefore antioxidant), modulate DNA repair, alter cellular metabolism, influence anti-inflammatory and finally anti-angiogenic activity 42 . Despite these myriad of beneficial actions, supplementation of NAC (2.5 mM 43 ) in our culture system failed to significantly improve the response of ETP treated MII oocytes. Thus, γH2A.X related fluorescence remained equivalent in both ETP/NAC exposed oocytes and those exposed to the ETP insult alone (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…These attributes include its capacity to act as a nucleophile (and therefore antioxidant), modulate DNA repair, alter cellular metabolism, influence anti-inflammatory and finally anti-angiogenic activity 42 . Despite these myriad of beneficial actions, supplementation of NAC (2.5 mM 43 ) in our culture system failed to significantly improve the response of ETP treated MII oocytes. Thus, γH2A.X related fluorescence remained equivalent in both ETP/NAC exposed oocytes and those exposed to the ETP insult alone (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…At the time of publication, over forty-five of the described jadomycins have been evaluated for biological activity, including various cancer cytotoxicity assays [7][8][9][10]13,15,[17][18][19][20]25,[32][33][34][35] and antimicrobial panels. 6,20,33,34 Jadomycins have been implicated in the inhibition of aurora kinase B 10,54 and topoisomerases.…”
Section: Looking Forwardmentioning
confidence: 99%
“…6,20,33,34 Jadomycins have been implicated in the inhibition of aurora kinase B 10,54 and topoisomerases. 8,55 Other studies have demonstrated DNA-cleavage by jadomycin through a generation of reactive oxygen species in the presence of Cu(II), 9,17,18,25,56 although further studies have concluded that ROS-dependant mechanisms are not the primary contributor to bioactivity. 8 In triple negative breast cancer cell lines, jadomycins have shown resistance of drug efflux mechanisms.…”
Section: Looking Forwardmentioning
confidence: 99%
See 2 more Smart Citations